The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.22495/cgobrv6i2sip11
|View full text |Cite
|
Sign up to set email alerts
|

Negative reflections of nepotism on employees and obstacles in the process of institutionalization of family businesses

Abstract: One of the most prominent problems faced by family businesses is the presence of nepotism. This study was conducted to find out if nepotism is present in local family businesses operating in Kosovo. It also aims to identify the negative reflections of nepotism on employees and the effects of nepotism on obstructing the institutionalization of family businesses. In this study, direct interviews were conducted with the managers of 10 family businesses who have no family ties with the founders of the business. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
0
0
0
Order By: Relevance
“…Supporting this notion, Spahi (Spahi et al, 2022) identified the negative consequences of nepotism on managers and employees in Kosovo. Similarly, (Sugundan et al, 2018) emphasized the detrimental nature of nepotism, describing it as a "very unhealthy practice" that disrupts human resource recruitment and demotivates non-family employees.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Supporting this notion, Spahi (Spahi et al, 2022) identified the negative consequences of nepotism on managers and employees in Kosovo. Similarly, (Sugundan et al, 2018) emphasized the detrimental nature of nepotism, describing it as a "very unhealthy practice" that disrupts human resource recruitment and demotivates non-family employees.…”
Section: Discussionmentioning
confidence: 92%
“…This pervasive nature of nepotism presents a significant challenge for Ugandan family businesses, as widely discussed in various publications. Notably, research by Spahi (Spahi et al, 2022) identifies nepotism as a leading cause of decreased employee motivation. While only 35.8% of respondents denied the existence of nepotism altogether, a substantial portion (64.3%) acknowledged its presence, highlighting its potential impact on Ugandan family businesses.…”
Section: Discussionmentioning
confidence: 99%